The Rapid Plasma Reagin Test Cannot Replace the Venereal Disease Research Laboratory Test for Neurosyphilis Diagnosis - Marra, Christina M. (2012)
BACKGROUND: The cerebrospinal fluid (CSF) Venereal Disease Research Laboratory (VDRL) test is a mainstay for neurosyphilis diagnosis, but it lacks diagnostic sensitivity and is logistically complicated. The Rapid Plasma Reagin (RPR) test is easier to perform, but its appropriateness for use on CSF is controversial. METHODS: RPR reactivity was determined for CSF from 149 individuals with syphilis using two methods. The CSF-RPR was performed according to the method for serum. The CSF RPR-V was performed using the method recommended for the CSF-VDRL. Laboratory defined neurosyphilis included reactive CSF-Fluorescent Treponemal Antibody Absorption test and CSF white blood cells > 20/ul. Symptomatic neurosyphilis was defined as vision loss or hearing loss. RESULTS: CSF-VDRL was reactive in 45 (30.2%) patients. Of these, 29 (64.4%) were CSF-RPR reactive and 37 (82.2%) were CSF-RPR-V reactive. There were no instances where the CSF VDRL was nonreactive but the CSF-RPR or CSF-RPR-V was reactive. Among the 28 samples that were reactive in all three tests, CSF-VDRL titers (median [IQR], 1:4 [1:4-1:16]) were significantly higher than CSF-RPR (1:2 [1:1-1:4], p=0.0002) and CSF-RPR-V titers (1:4 [1:2-60 1:8], p=0.01). The CSF RPR and the CSF-RPR-V tests had lower sensitivities than the CSF VDRL: 56.4% and 59.0% vs. 71.8% for laboratory-diagnosed neurosyphilis and 51.5% and 57.6% vs. 66.7% for symptomatic neurosyphilis. CONCLUSIONS: Compared to the CSF-VDRL, the CSF-RPR has a high false-negative rate, thus not improving upon this known limitation of the CSF-VDRL for neurosyphilis diagnosis. Adapting the RPR procedure to mimic the CSF-VDRL decreased, but did not eliminate, the number of false negatives, and did not avoid all the logistical complications of the CSF VDRL.